Pemaknaan Interaksi Parasosial dalam Livestreaming antara Membership Youtube dan Streamer di Platform Youtube Gojek Dota2 - Putra Sandy, Adam; Fitriana Poerana, Ana; Ramdhani, Muhammad (CV. ULIL ALBAB CORP, 2025)
The purpose of this study is to describe in detail the parasocial interaction between Gojek Dota2 streamers and their fans through the Youtube platform. What motivations do Gojek Dota2 youtube memberships have and their implications for the parasocial interaction between Gojek Dota2 streamers and their youtube memberships. This study uses a qualitative research method to explore the phenomenon of interaction between viewers and streamers in live streaming. The data sources in this study come from two main types of data, namely primary data and secondary data. Data analysis techniques in this study consist of data reduction, data display, and drawing conclusions. Based on the results of the study, the motives for becoming a Gojek Dota 2 YouTube membership are influenced by the desire to support streamers, interest in Dota 2 content, and the need for a community with similar interests. The informant stated that the decision was driven by emotional closeness, the intention to help, and the added value of the educational and entertainment content presented by Bang Fahri. Membership for them is not just a paid subscription, but a symbol of emotional involvement and a form of appreciation. They feel closer, involved in the community, and recognized through direct interactions on live streams and other platforms. Parasocial interactions in this community show strong emotional connections, although not entirely reciprocal, such as through name-calling, chat responses, donations, and play sessions together. Streamers play an important role in building these relationships. Bang Fahri not only presents content, but creates a family atmosphere and pays attention to members, so they feel comfortable, appreciated, and part of something bigger